Sustainable Mobility for Island Destinations - Tsoutsos, Theocharis; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This open access book presents the findings of the CIVITAS DESTINATIONS project regarding the link between mobility and tourism in urban areas and the complications tourist destinations face in becoming more sustainable. It integrates the tourist mobility needs and the associated fluctuation impacts in the design of mobility solutions in order to enforce the accessibility, attractiveness, efficiency and sustainability of transport services and infrastructure for both residents and tourists in island cities such as Rethymno, Crete, and Valetta, Malta. Sustainable Mobility for Island Destinations contains contributions from highly experienced academics, engineers, and planners in the area of sustainable tourism, mobility services, and smart solutions design companies assisting: the change of the mind set in insular and tourism areas; the adoption of green mobility systems and services; and monitoring the environmental benefits to assist towards the Climate Change. It explores the challenges tourist islands face, such as the seasonal fluxes in transport usage, the pressures of tourism to provide aesthetic green spaces, and the space issues of being an island in relation to economic potential and infrastructure construction. The book suggests areas for future research, and implementation of innovative systems and policies. It will be of interest to academics, planners, decision makers, and environmentalists.
Introduction -- Towards a Green Deal in Transport -- Sustainable Tourism and Mobility -- Sustainable Urban Mobility Plans for Guest and Citizens -- Greening the Public Transport -- Alternative Fuels and Practices -- Innovation, ITS and Tourism Destinations- Challenges for Business Models -- Micromobility in the Urban Environment -- Measuring Environmental Impact in Cities -- Insular Experiences and Challenges from Transport and Tourism.
Keywords: Transportation engineering; Traffic engineering; Energy policy; Energy and state; Environmental economics; Development economics; Transportation Technology and Traffic Engineering; Energy Policy, Economics and Management; Environmental Economics; Development Economics